Biomekhanicheskaya spetsifika utomleniya pri bege na 400 m - Arakelyan, E. E.; Primakov, Yu. N.; Tyupa, V. V.; Umarov, A. A.; Guseynov, F. A. (Teorija i Praktika fiziceskoj Kul'tury, 1997)
The aim of this study was to reveal the specific influence of a fatigue on running technique in 400 meters running. 115 runners of various qualification acted as subjects of the research. The obtained results allow to conclude that the specifics of the fatigue in running displays in the distriction of the relation between the power of muscles' contraction and stretching. The idea about the local muscle endurance had been confirmed, that can be used to improve the effectiveness of running in the conditions of the acute fatigue.